2021
DOI: 10.3390/min11020208
|View full text |Cite
|
Sign up to set email alerts
|

Measurement on Diffusion Coefficients and Isotope Fractionation Factors by a Through-Diffusion Experiment

Abstract: For radioactive waste disposal, it is important that local groundwater flow is slow as groundwater flow is the main transport medium for radioactive nuclides in geological formations. When the groundwater flow is very slow, diffusion is the dominant transport mechanism (diffusion-dominant domain). Key pieces of evidence indicating a diffusion-dominant domain are the separation of components and the fractionation of isotopes by diffusion. To prove this, it is necessary to investigate the different diffusion coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…smallest pore in high-tension area). We do not distinguish between specific diffusion coefficients for δ 2 H and δ 18 O, as Hasegawa et al (2021) recently found generally equal diffusion properties of both isotopes in artificial and natural porous media.…”
Section: Simulation With the Dipmi Approachmentioning
confidence: 78%
See 1 more Smart Citation
“…smallest pore in high-tension area). We do not distinguish between specific diffusion coefficients for δ 2 H and δ 18 O, as Hasegawa et al (2021) recently found generally equal diffusion properties of both isotopes in artificial and natural porous media.…”
Section: Simulation With the Dipmi Approachmentioning
confidence: 78%
“…The latter situation is the case when simulating the diffusive spreading of common solute tracers (e.g. bromide or chloride) in porous media, because diffusion coefficients of the dissolved solute molecules are usually smaller compared to those of pure water or stable water isotopes (Hasegawa et al, 2021).…”
Section: Analysis Of the Virtual Experimentsmentioning
confidence: 99%
“…Pore-size-distributed D values thus range from ~ 1.9 • 10 -9 m² s -1 in bin 1 (= largest pore in low-tension area) to ~ 9.0 • 10 -12 m² s -1 in bin 200 (= smallest pore in high-tension area). We do not distinguish between specific diffusion coefficients for δ²H and δ 18 O, as Hasegawa et al (2021) recently found generally equal diffusion properties of both isotopes in artificial and natural porous media. 10…”
Section: Simulation With the Dipmi Approach 25mentioning
confidence: 85%
“…In the investigated Wakkanai formation, natural groundwater flow has been shown to be extremely slow, with a component of palaeo-seawater still preserved in the porewater 50 . In the matrix of the Wakkanai formation, the transport of solutes will be diffusion-dominated 51 . The distance over which Ca may be transported by diffusion can be estimated using the following equation 52 :…”
mentioning
confidence: 99%
“…In the matrix of the Wakkanai formation D = 10 −10 m 2 /s (based on through-diffusion experiments using non-sorbing tracers 51 ). Equation ( 1) then gives a maximum distance of Ca diffusion through the matrix of about 10 cm over 17 months.…”
mentioning
confidence: 99%